Reprints of Rare Papers on Mollusca: Martin Lister (1678) Historiae Animalium Angliae - Martin Lister (Hello World!, 1971)
In this number of Sterkiana the first plate is not reproduced since it deals with spiders and accompanied Lister's text on that group of arthropods. The next four plates are reproduced here without reduction. They show living forms, not all of them Mollusca, and the last four are of fossils Mollusca, Brachiopoda, Echinoidea, and others.